Characterization and therapeutic perspectives of differentiation-inducing therapy in malignant tumors - Zhu, Kangwei; Xia, Yuren; Tian, Xindi; He, Yuchao; Zhou, Jun; Han, Ruyu; Guo, Hua; Song, Tianqiang; Chen, Lu; Tian, Xiangdong (Frontiers in Genetics, 2023)
Cancer is a major public health issue globally and is one of the leading causes of death. Although available treatments improve the survival rate of some cases, many advanced tumors are insensitive to these treatments. Cancer cell differentiation reverts the malignant phenotype to its original state and may even induce differentiation into cell types found in other tissues. Leveraging differentiation-inducing therapy in high-grade tumor masses offers a less aggressive strategy to curb tumor progression and heightens chemotherapy sensitivity. Differentiation-inducing therapy has been demonstrated to be effective in a variety of tumor cells. For example, differentiation therapy has become the first choice for acute promyelocytic leukemia, with the cure rate of more than 90%. Although an appealing concept, the mechanism and clinical drugs used in differentiation therapy are still in their nascent stage, warranting further investigation. In this review, we examine the current differentiation-inducing therapeutic approach and discuss the clinical applications as well as the underlying biological basis of differentiation-inducing agents.